2013
DOI: 10.2147/ijn.s38708
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth oxide aqueous colloidal nanoparticles inhibit Candida albicans growth and biofilm formation

Abstract: Multiresistance among microorganisms to common antimicrobials has become one of the most significant concerns in modern medicine. Nanomaterials are a new alternative to successfully treat the multiresistant microorganisms. Nanostructured materials are used in many fields, including biological sciences and medicine. Recently, it was demonstrated that the bactericidal activity of zero-valent bismuth colloidal nanoparticles inhibited the growth of Streptococcus mutans; however the antimycotic potential of bismuth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 47 publications
(40 reference statements)
2
19
0
Order By: Relevance
“…Regarding C. albicans , the calculated IC 50 value for BiNPs against biofilms formed by this fungus was 7.9 µg mL -1 , which interestingly is very close to its value under planktonic conditions As far as the authors know, the antibiofilm activity of BiNPs only has been addressed in one other study, where a concentration of 418 µg mL -1 was required to inhibit the C. albicans biofilm. [55]. When compared to antifungal agents.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding C. albicans , the calculated IC 50 value for BiNPs against biofilms formed by this fungus was 7.9 µg mL -1 , which interestingly is very close to its value under planktonic conditions As far as the authors know, the antibiofilm activity of BiNPs only has been addressed in one other study, where a concentration of 418 µg mL -1 was required to inhibit the C. albicans biofilm. [55]. When compared to antifungal agents.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, doses of 100 mg mL −1 and 0.932 mg•mL −1 of Bi 2 O 3 NPs induced no cytotoxicity in murine periodontal ligament and rat osteosarcoma cells and monkey kidney cells, respectively. 42 , 43 …”
Section: Toxicitymentioning
confidence: 99%
“…Studies have shown that bismuth derivatives and its nanoparticulate forms inhibit Helicobacter pylori growth by altering their Krebs cycling, amino acid, and nucleotide metabolisms, and they can be used as an antidiarrheal agent to treat nausea, vomiting, and stomach pain [ 22 ]. Additionally, it was reported that BiNPs exhibited antibacterial and antifungal activities at concentrations lower than 1 mM and 2 mM, respectively [ 23 , 24 ]. Also, they can interfere with the biofilm formation of S. mutans , the main etiological agent of dental decays [ 23 ].…”
Section: Introductionmentioning
confidence: 99%